D-Dimer Determination to Assess Regression of Deep Venous Thrombosis - Janssen, M C H; Verbruggen, H; Wollersheim, H; Hoogkamer, B; van Langen, H; Nováková, I R O (Thrombosis and Haemostasis, 1997)
A number of studies evaluating deep venous thrombosis (DVT) have demonstrated that plasma levels of thrombotic and fibrinolytic parameters change during treatment, but the relationship between thrombus regression and evolution of these markers remains unknown. The objective of the present study was to correlate levels of D-Dimer (DD) with thrombus regression as assessed by duplex scanning.From 44 patients treated for acute DVT, DD were determined at diagnosis and at the end of initial heparin therapy of at least 5 days. Thrombus regression was measured by repeated duplex scanning at diagnosis and after 1 and 3 months.DD significantly decreased during heparin treatment as compared with values at presentation. DD levels were significantly higher in the group of patients without normalization of the DVT after 3 months (p = 0.003). A ninefold excess tendency was seen for DD levels > 1200 ng/ml at the end of initial treatment to be associated with poor resolution of the DVT [odds ratio 9.0, 0.95 confidence interval (CI) 2.3-35.4]. When the patients with an established malignancy were excluded, the differences were even more significant (p = 0.0004 for DD levels after initial treatment and an odds ratio of 17.5, 0.95 CI 3.3-92.5).These results suggest that increased DD levels after the initial phase of treatment are related to poor resolution of DVT after 3 months. These findings contribute to further insight into the process of thrombus regression. Furthermore high DD levels might help to identify the patients with a poor prognosis and could be useful to judge the efficacy of anticoagulant treatment.